Effect of Polymer Modification Bitumen on Performance of Flexible Pavement in Hot Arid Area in Libya - Hassan Awadat Salem (Wadi Alshatti University Journal of Pure and Applied Sciences, 2025)
Premature rutting of flexible pavements is a significant problem faced by Libya, which has over 83200 km of national highways. Bituminous surfacing as a wearing course is commonly used for flexible pavements in Libya. This study aims to evaluate the effectiveness of polymer modification using Superpave and European mix design methods. The study includes binder characterization, PG determination, and several mechanical tests such as Water Sensitivity, Wheel Tracking, and Stiffness Modulus. The "Dry Process" SBS-modified mixture showed better results than the traditional unmodified asphalt concrete. The study shows that using more PR FLEX 20® increases the high-temperature PG value and reduces the rutting phenomenon. The study also proposes guidelines for implementing Polymer Modified Asphalt (PMA) concrete in Libya and suggests that Superpave technology can be adopted to design flexible pavement in the country.